Free Flap Reconstruction of the Extremities in Patients Who are ≥65 Years Old: A Single-Center Retrospective 1-to-1 Matched Analysis - Spindler N (Dove Medical Press, 2021)
Nick Spindler, Philipp Pieroh, Ulrich Spiegl, Sergey Arakelyan, Johannes Karl Maria Fakler, Christoph-Eckhard Heyde, Stefan Langer Department of Orthopedic Surgery, Traumatology and Plastic Surgery, University Hospital Leipzig, Leipzig, GermanyCorrespondence: Nick SpindlerDepartment of Orthopedic Surgery, Traumatology and Plastic Surgery, University Hospital Leipzig, Liebigstrasse 20, Leipzig, 04103, GermanyTel +49-341-9717140Fax +49-341-9717139Email nick.spindler@medizin.uni-leipzig.dePurpose: Demographic changes are leading to population aging, and free flap reconstructions for various indications are expected to become increasingly common among older patients. Therefore, this study evaluated free flap reconstruction of the extremities in older patients and compared the outcomes to those from younger patients who underwent similar procedures during the same period.Patients and Methods: This single-center retrospective study used a case-control design to compare older and younger patients who underwent free flap reconstruction of soft tissue defects in the extremities. One-to-one matching was performed for older patients (≥ 65 years) and younger patients (≤ 64 years) according to indication, flap recipient site, and flap type. The parameters of interest were clinico-demographic characteristics, flap type, defect location, indication for free flap reconstruction, number of venous anastomoses, and postoperative complications (flap loss, infection, and wound healing disorders).Results: The study included 48 older patients and 133 younger patients, with a mean follow-up of 12 months after discharge. The free flap reconstruction was performed at a mean interval of 19.8± 22.8 days (range: 0– 88 days). The 1:1 matching created 38 pairs of patients, which revealed no significant differences in the rates of flap necrosis and flap failure.Conclusion: This study failed to detect a significant age-related difference in the flap necrosis rate after free flap reconstruction of extremity defects. Therefore, with careful perioperative management and patient selection, microsurgical free flap reconstruction is a feasible option for older patients.Keywords: older patients, microsurgery, free flap, limb reconstruction